Maternal Proinflammatory Adipokines Throughout Pregnancy and Neonatal Size and Body Composition: A Prospective Study. Issue 10 (7th September 2021) - Francis, Ellen C; Li, Mengying; Hinkle, Stefanie N; Chen, Jinbo; Wu, Jing; Zhu, Yeyi; Cao, Haiming; Tsai, Michael Y; Chen, Liwei; Zhang, Cuilin
ABSTRACT: Background: Increased maternal adiposity and inflammation have impacts on fetal growth. Objectives: The purpose of this prospective study was to investigate the associations of 3 proinflammatory adipokines in pregnancy with neonatal anthropometry. Methods: In a sample of 321 US pregnant women from the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) Fetal Growth Studies-Singleton Cohort (NCT00912132), plasma IL-6, fatty acid binding protein-4 (FABP4), and chemerin were measured in plasma samples collected at 10–14, 15–26, 23–31, and 33–39 weeks of gestation. Generalized linear models were used to estimate associations of adipokines with neonatal weight, thigh, and crown-heel length, and skinfolds at birth. Models adjusted for age, race/ethnicity, education, nulliparity, prepregnancy BMI, and weeks of gestation at blood collection. Results: At each time point, higher IL-6 was associated with lower neonatal birthweight and thigh length. At 15–26 weeks of gestation, a 1 SD pg/mL increase in IL-6 was associated with –84.46 g lower neonatal birthweight (95% CI: –150.70, –18.22), –0.17 cm shorter thigh length (95% CI: –0.27, –0.07), –0.43 cm shorter crown-heel length (95% CI: –0.75, –0.10), and –0.75 mm smaller sum of skinfolds (95% CI: –1.19, –0.31), with similar associations at 23–31 and 33–39 weeks of gestation. There were no associations of FABP4 and chemerin with neonatal anthropometry. Conclusions: Starting as early as 15 weeks of gestation, higher maternal IL-6 concentrations in pregnancy were associated with lower neonatal birthweight, thigh and crown-heel length, and skinfolds. These data provide insight into the relevance of maternal inflammatory markers with neonatal anthropometry. Abstract : Beginning in early pregnancy and throughout gestation, higher IL-6, a marker of inflammation, was associated with lower newborn weight, shorter length, and smaller skin folds.